2020
DOI: 10.1080/15299716.2020.1791300
|View full text |Cite
|
Sign up to set email alerts
|

Young Bisexual People’s Experiences of Sexual Violence: A Mixed-Methods Study

Abstract: Bisexual people are at an increased vulnerability for sexual victimization in comparison to heterosexual people, as well as gay and lesbian people. As the majority of first sexual violence experiences happen prior to age 25 for bisexual women, young bisexual people are particularly vulnerable. Despite consistent evidence of this health disparity, little is known about what factors might increase young bisexual people's risk for sexual victimization, or how they access support post-victimization. The current st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…These preliminary findings suggest that SM women are not being assaulted by other women, but rather men. Our findings reflect prior research (Flanders et al, 2020). SM women's sexual perpetrators may be more likely to be men because our SM group is primarily comprised of women who identify as bisexual (16% of women in the SM group identified as bisexual) and bisexual women are at the highest risk of experiencing sexual assault compared with other SM identities (Canan et al, 2019;Flanders et al, 2019;Hequembourg et al, 2013).…”
Section: Substance Use and Nonconsensual Sexsupporting
confidence: 80%
See 2 more Smart Citations
“…These preliminary findings suggest that SM women are not being assaulted by other women, but rather men. Our findings reflect prior research (Flanders et al, 2020). SM women's sexual perpetrators may be more likely to be men because our SM group is primarily comprised of women who identify as bisexual (16% of women in the SM group identified as bisexual) and bisexual women are at the highest risk of experiencing sexual assault compared with other SM identities (Canan et al, 2019;Flanders et al, 2019;Hequembourg et al, 2013).…”
Section: Substance Use and Nonconsensual Sexsupporting
confidence: 80%
“…For instance, women's internalisation of bisexual stigma (e.g. 'people do not take me seriously when I tell them I am bisexual') was associated with an increased risk of sexual assault victimisation (Flanders et al, 2020). Additionally, having experiences where someone else stigmatised or mistreated someone who identified as bisexual was also associated with an increased risk of sexual victimisation for the person who identified as bisexual (Flanders et al, 2020(Flanders et al, , 2019.…”
Section: Substance Use and Nonconsensual Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Flanders et al (2019) reported that among a sample of bi+ women, bisexual stigma was positively associated with increased reports of sexual violence. A mixed-method study of young bisexual people replicated these findings both qualitatively and quantitatively (Flanders et al, 2020). Further, both bisexual stigma and internalized heterosexism have been found to be associated with greater odds of experiencing verbal sexual coercion among bisexual women (Salim et al, 2020).…”
Section: Sexual Violence Disparitiesmentioning
confidence: 72%
“…The data reported in this article were from a larger mixed-methods project investigating the sexual victimization experiences and mental health of young bisexual people aged 18 to 25 (Flanders, Anderson, & Tarasoff, in preparation). All study procedures were reviewed and approved by the Institutional Review Board of Mount Holyoke College.…”
Section: Methodsmentioning
confidence: 99%